The Relationship between Trust and Family Empowerment to Prevent Transmission of Pulmonary Tuberculosis - Nirmala Kusumaningrum Sunaryo; Joni Haryanto; Florentina Sustini (International Journal of Nursing and Health Services (IJNHS), 2020)
Tuberculosis (TB) is infectious diseases directly caused by TB bacteria (Mycobacterium tuberculosis). Tuberculosis has been around for thousands of years and remains a significant issue of global health issues. This study aimed to analyze the relationship between trust and family empowerment in preventing pulmonary TB transmission. A cross-sectional design was applied in this study. The results showed that there was a relationship between trust and family empowerment to avoid the transmission of pulmonary TB (p-value = 0.028). Health workers needed to concern about this transmission of diseases and educated of family members on the transmission of pulmonary TB.